Benzimidazole functionalization enables efficient multi-resonance TADF with accelerated spin-flipping and balanced charge transport - Ji-Hua Tan; Si-Wei Chen; Xin-Lu Li; Han-Nan Shi; Xiao-Long Liu; Yao-Zu Su; Xiaofeng Wang; Jun-Hua Zhuang; Chengxiang Shi; Jia-Ming Jin; Shaoyun Yin; Jia-Xiong Chen; et al. (Chemical Engineering Journal, 2026)

Evolution of fine structure and pasting properties in wheat starch during medium-high-temperature Daqu fermentation - Zhenbing Ma; Yuanyuan Tian; Dong Zhao; Lihua Zhao; Jia Zheng; Jian Su; Yanping Lu; Yi Ma (Food Research International, 2026)

Inflammation-targeted bioactive SiMo glass-ceramic nanozymes for adaptive and sequential infection-impaired wound repair through precise immunoregulation and antiinfection - Jing Tian; Yanzi Zhao; Yanping Zuo; Xiaochen Su; Long Zhang; Weipeng Qiang; Zuhao Zhang; Minhui Ai; Houjin Zhuang; Qian Huang; Meng Luo; Bo Lei (Chemical Engineering Journal, 2026)

Numerical investigation of local convective heat transfer coefficients for a walking human model under varying wind directions - Qigui Zhou; Xiaowen Su; Yanping Yuan; Dengkai Chen; Fujian Jiang (Building and Environment, 2026)

Comprehensive analysis of lactones and furanones in baijiu: Identification, quantitation, sensorial contribution and aging-related insights - Hao Huang; Yi Li; Huijing Lan; Jia Zheng; Dong Zhao; Jian Su; Yanping Lu; Shuang Chen; Yan Xu (Food Research International, 2026)

Characteristics of sediment microbial community structure under different vegetation types with various restoration durations in Hongze Lake - Yuhan Jin; Wangting Yang; Yuling Yang; Yanping Wang; Huaiping Ling; Sile Wen; Bingjie Ren; Xiuling Zhang; Zhenfa Su; Jinghao Jin; Yuzhi Song; Lidong Shen (Journal of Environmental Management, 2026)

Comammox Nitrospira dominates autotrophic nitrification in paddy fields under long-term fertilization - Bingjie Ren; Yanping Wang; Yuchao Wang; Yuling Yang; Zhenfa Su; Haikun Wu; Wangting Yang; Yuhan Jin; Jinghao Jin; Shuai Liu; Lidong Shen; Xu Zhao (Agriculture, Ecosystems & Environment, 2026)

Ethylene production from chlorinated organic hazardous wastes by thermal plasma pyrolysis - Yanping Yu; Hao Li; Wenlong Dong; Jiachen Zhu; Jiaqi Xu; Chen Wang; Baogen Su; Wenjun Zhang; Zhongbiao Wu; Qilong Ren; Qiwei Yang (Journal of Hazardous Materials, 2026)

Low-dose nano superhydrophobic materials modulate soil health: Dose-dependent trade-offs in microbial communities and plant responses - Linna Du; Xinyi Fang; Xingyu Gong; Yanping Xiao; Fengzhan Tang; Jiacheng Zhou; Mengjie Gu; Ying Su; Yongsheng Song (Journal of Soils and Sediments, 2026)

Advances in acetylcholinesterase-based biosensing technologies for organophosphorus pesticide detection: A comprehensive review (2020–2024) - Qian Zhang; Jing Yu; Yanping Wei; Rong Yang; Jin Liu; Yangyang Su; Die Gao; Jing Zeng (Food Chemistry, 2025)

Analysis of human electroencephalogram features in hypobaric oxygen-enriched environments - Mingxi Yang; Xuanyuan Gou; Liangliang Sun; Xiaowen Su; Yanping Yuan (Building and Environment, 2025)

Expert consensus on cryosurgery therapy of mucosal melanoma on head and neck - Yadong Wu; Guoxin Ren; Moyi Sun; Zhangui Tang; Longjiang Li; Jian Meng; Zhijun Sun; Shaoyan Liu; Yue He; Wei Shang; Bo Li; Jie Zhang; et al. (Cryobiology, 2025)

A novel method of calculating mean skin temperature with high thermal sensitivity for thermal sensation evaluation - Xiaowen Su; Ongun Berk Kazanci; Bjarne W. Olesen; Liangliang Sun; Yanping Yuan (Energy and Buildings, 2025)

Polyphenylene molecular engineering enables highly efficient multi-resonance thermally activated delayed fluorescence emitters with quenching resistance - Longjiang Xing; Xiaofeng Wang; Xiaolong Liu; Wen-Cheng Chen; Shihao Liu; Siwei Chen; Mengke Li; Ji-Hua Tan; Jia-Ming Jin; Ruicheng Wang; Shangru Li; Shaomin Ji; et al. (Chemical Engineering Journal, 2025)

Paracoccus yibinensis sp. nov., a novel bacterium with astaxanthin producing isolated from the environment of Chinese distilled Baijiu - Qingchun Luo; Yanping Lu; Xi Li; Jian Su; Pengju Zhao; Zhu Zhang; Yang Gu; Dong Zhao; Jia Zheng (Antonie van Leeuwenhoek, 2025)

Fluorinated Zn-porphyrin covalent organic frameworks with optimized hydrophobic/hydrophilic balance towards stable Zn anodes - Xia Li; Yanping Chu; Shouliang Lu; Liangdan Chen; Long Su; Fei Lu; Zhen Chen; Xinpei Gao (Chemical Engineering Journal, 2025)

Temporal dynamics of summer phytoplankton communities and their response to environmental changes in the northern Yellow Sea (2011-2020) - Yibo Wang; Zhiliang Liu; Yanping Qi; Yang Chen; Haibo Zhang; Xihan Liu; Du Su (Frontiers in Marine Science, 2025)
Research on phytoplankton distribution and dynamics is crucial for understanding marine ecosystem functions and evaluating their status. The northern Yellow Sea (NYS), a marginal sea of the Pacific Ocean, has experienced significant anthropogenic impacts since the late 20 th century, resulting in an increased nitrogen-to-phosphorus (N/P) ratio and heightened phosphorus limitation. These changes are considered critical factors affecting the phytoplankton community structure in the NYS over recent decades. This study analyzed the temporal dynamics of environmental factors and phytoplankton community structure in the NYS during the summers from 2011 to 2020, aiming to elucidate recent changes in phytoplankton community structure and their driving forces. The results indicated a significant decrease in dissolved inorganic nitrogen (DIN) concentration after 2011, resulting in a decreased N/P ratio, while phosphorus limitation persisted. Temperature, temperature gradient (reflecting stratification intensity) and salinity exhibited upward trends, whereas pH, nitrogen-to-silicon (N/Si) ratio, and chlorophyll- a concentration showed downward trends. The abundances of total phytoplankton, Bacillariophyta, and Dinoflagellata, as well as the Dia/Dino index, fluctuated annually and correlated with temperature, temperature gradient, and nutrient structure. Diversity indices remained stable throughout the study period. The Yellow Sea Cold Water Mass prominently influenced summer phytoplankton community structure, exhibiting lower phytoplankton abundance, Dia/Dino index, and species richness in the cold water mass region, where adaptable species such as Tripos muelleri and Paralia sulcata predominated. Our results emphasized the impact of environmental changes associated with climate change, including rising temperatures, increased salinity, and enhanced stratification, on the phytoplankton community structure in recent years, particularly concerning the dominant species composition and the Dia/Dino index. Therefore, ongoing attention to the effects of climate change on coastal environments and phytoplankton communities is essential.

Hexagonal liquid crystals as emerging quasi solid-state electrolytes for aqueous lithium-ion batteries - Weirong Ren; Zhaowei Hou; Long Su; Xinpei Gao; Yanping Chu; Liqiang Zheng; Fei Lu (Chemical Engineering Journal, 2024)

Effects of hypobaric hypoxia on human physiological and psychological responses in hot-humid environments - Yue Hu; Liangliang Sun; Guorong Xu; Xiaowen Su; Yanping Yuan (Building and Environment, 2024)

Field experiment on transient thermal comfort in a Chinese railway station – High temperature exposures - Xiaowen Su; Wei Liu; Richard de Dear; Liangliang Sun; Yanping Yuan (Building and Environment, 2024)

The modulation of proteomics and antioxidant stress is involved in the effect of nitazoxanide against Japanese encephalitis virus in vitro - Yu Su; Yanping Wang; Chengeng Xiong; Xiaoyang Wang; Chunmei Wang; Wen Zhou; Donghai Zhou; Keyu Zhang (Veterinary Microbiology, 2024)

Removal of calcium from phosphoric acid produced by the nitric acid process using solvent extraction with TCHDGA and stripping with water - Chengjin Xu; Miaomiao Zhang; Jianhui Su; Xiujing Peng; Xiangfeng Kong; Yanping Luo; Jiahui Sun; Yu Cui; Xuchuan Jiang; Guoxin Sun (Hydrometallurgy, 2024)

Proton transfer induced persistent triplet charge transfer phosphorescence in molecule-doped polymer systems - Shulin Liu; Chensheng Li; Liyun Liao; Yanping Huo; Zhong-Min Su; Fu-Shun Liang; Yingxiao Mu (Chemical Engineering Journal, 2024)

Response of phytoplankton communities to environmental changes in the Bohai Sea in late summer (2011–2020) - Yibo Wang; Zhiliang Liu; Yanping Qi; Xiao Chen; Yang Chen; Du Su; Xiaobo Yuan; James Klippel-Cooper (Acta Oceanologica Sinica, 2024)

A newly-discovered tea population variety processed Bai Mu Dan white tea: Flavor characteristics and chemical basis - Yanping Lin; Yibiao Huang; Su Zhou; Xiaolan Li; Yike Tao; Yani Pan; Xinyu Feng; Haowei Guo; Ping Chen; Qiang Chu (Food Chemistry, 2024)

Highly stable ultralong organic phosphorescence from a 3D organic supramolecule constructed by halogen bonding and π–π interactions - Aiping Yao; Jing Gao; Yingxiao Mu; Guangfu Li; Kuizhan Shao; Guogang Shan; Yun Geng; Yanping Huo; Zhongmin Su; Xinlong Wang (Chemical Engineering Journal, 2024)

Determining the response of ecological drought to meteorological and groundwater droughts in Northwest China using a spatio-temporal matching method - Tianliang Jiang; Xiaoling Su; Yanping Qu; Vijay P. Singh; Te Zhang; Jiangdong Chu; Xuexue Hu (Journal of Hydrology, 2024)

Exploration of 5-Azacytidine and Trichostatin A in the modulation of postharvest quality of 'Shine Muscat' grape berries - Haoran Jia; Ziwen Su; Yanhua Ren; Dan Pei; Kun Yu; Tianyu Dong; Yanping Zhang; Haifeng Jia (Postharvest Biology and Technology, 2024)

Structures and ion transport mechanisms of plant high-affinity potassium transporters - Jiangqin Wang; Yanping Luo; Fan Ye; Zhong Jie Ding; Shao Jian Zheng; Shuai Qiao; Yong Wang; Jiangtao Guo; Wei Yang; Nannan Su (Molecular Plant, 2024)

Identification, characterisation and expression analysis of peanut sugar invertase genes reveal their vital roles in response to abiotic stress - Tingting Mao; Yaru Zhang; Wenwen Xue; Yu Jin; Hongfei Zhao; Yibo Wang; Shengnan Wang; Shengjie Zhuo; Feifei Gao; Yanping Su; Chunyan Yu; Xiaotong Guo; et al. (Plant Cell Reports, 2024)

Highly Sensitive Detection of PIK3CA Mutations by Looping-Out Probes-Based Melting Curve Analysis - Boheng Xu; Yanping Lan; Danjiao Luo; Yangsi Zheng; Runfang Ni; Guoqiang Su; Qiuying Huang; Qingge Li (Biochemical Genetics, 2024)

Effects of saline water with different concentrations of calcium and magnesium ions on emitter clogging in drip irrigation integrated water–fertilizer system - Long Zhou; Chenchen Wei; Peiling Yang; Yunkai Li; Lili Zhangzhong; Yanping Su; Xin Wang; Xin He (Irrigation and Drainage, 2024)
The application of saline water in drip irrigation is severely constrained due to its high salt content, which causes precipitation and emitter clogging. Therefore, the effects of calcium and magnesium ions at 100, 150 and 200 mg/L in saline water coupled with humic acid nitrogen fertilizer on emitter clogging were studied. Compared with ground saline water, all treatments significantly increased the emitter clogging risk. In the calcium and magnesium ion treatment groups, clogging fouling increased by 23.94–58.35 and 14.55–51.21 mg/cm 2 , the discharge variation ratio (Dra) decreased by 22%–59% and 14%–49%, and the Christiansen coefficient of uniformity (CU) decreased by 29%–79% and 15%–74%, respectively. Higher ion concentrations caused more clogging. Saline water with a high calcium content caused more clogging. Under similar concentration conditions, the Dra and CU in high magnesium saline water were 9%–32% and 8%–51% higher, respectively. In addition, the increase in magnesium ion concentration changed the crystal form of carbonate, slowed the formation rate of precipitated dirt and significantly reduced the carbonate content by 19%–40%. Our results provide support for the popularization of saline water drip irrigation systems.

A multifunctional emitter with synergistical adjustment of rigidity and flexibility for high-performance data-recording and organic light-emitting devices with “hot exciton” channel - Guowei Chen; Wen-Cheng Chen; Yaozu Su; Ruicheng Wang; Jia-Ming Jin; Hui Liang; Bingxue Tan; Dehua Hu; Shaomin Ji; Hao-Li Zhang; Yanping Huo; Yuguang Ma (Chemical Engineering Journal, 2024)

Study on thermal properties of bio-char prepared by photo-thermal pyrolysis - Dexin Huang; Yankui Wang; Gongxiang Song; Song Hu; Hanjian Li; Yanping Zhang; Yi Wang; Sheng Su; Saad A. El-Sayed; Jun Xiang (Biomass and Bioenergy, 2023)

Manipulating critical memory periods to treat psychiatry disorders - Jiahui Deng; Xiao Lin; Yongbo Zheng; Sizhen Su; Xiaoxing Liu; Kai Yuan; Le Shi; Yanping Bao; Lin Lu (Science Bulletin, 2023)

Local thermal comfort chart for non-uniform building environments: Comparison with vehicle environments and its application - Xiaowen Su; Ongun Berk Kazanci; Zhaojun Wang; Bjarne W. Olesen; Liangliang Sun; Yanping Yuan (Building and Environment, 2023)

Carbonate dynamics in a tropical coastal system in the South China Sea featuring upwelling, river plumes and submarine groundwater discharge - Wei Yang; Xianghui Guo; Zhimian Cao; Jianzhong Su; Liguo Guo; Lifang Wang; Yi Xu; Tao Huang; Yan Li; Yanping Xu; Zhe Wang; Guizhi Wang; et al. (Science China Earth Sciences, 2022)

Dynamic agricultural drought risk assessment for maize using weather generator and APSIM crop models - Yaxu Wang; Juan Lv; Hongquan Sun; Huiqiang Zuo; Hui Gao; Yanping Qu; Zhicheng Su; Xiaojing Yang; Jianming Yin (Natural Hazards, 2022)

Hyperspectral anomaly detection based on score-guided cooperative autoencoders - Minkai Hou; Tao Wang; Yanzhao Su; Yanping Cai; Yiting Wang (International Journal of Remote Sensing, 2022)

X-ray Irradiation Improves Neurological Function Recovery of Injured Spinal Cord by Inhibiting Inflammation and Glial Scar Formation - Yi Wang; Yanping Niu; Fanguo Lin; Peng Su; Liesong Chen; Dong Liu; Yongming Sun (Journal of Molecular Neuroscience, 2022)

Hyperspectral anomaly detection based on adaptive weighting method combined with autoencoder and convolutional neural network - Minkai Hou; Tao Wang; Yanzhao Su; Yanping Cai; Jiping Cao (International Journal of Remote Sensing, 2022)

Formulation and Pharmacokinetic Evaluation of a Drug-in-Adhesive Patch for Transdermal Delivery of Koumine - Yanping Su; Wenxiang Lu; Xiaoling Fu; Ying Xu; Lixiang Ye; Jian Yang; Huihui Huang; Changxi Yu (AAPS PharmSciTech, 2020)

Genetic dynamics of earlier maturity group emergence in south-to-north extension of Northeast China soybeans - Mengmeng Fu; Yanping Wang; Haixiang Ren; Weiguang Du; Deliang Wang; Rongjun Bao; Xingyong Yang; Zhongyan Tian; Lianshun Fu; Yanxi Cheng; Jiangshun Su; Bincheng Sun; et al. (Theoretical and Applied Genetics, 2020)

Active Biomonitoring of Metals with Cultured Anodonta woodiana: A Case Study in the Taihu Lake, China - Xiubao Chen; Yanping Su; Hongbo Liu; Jian Yang (Bulletin of Environmental Contamination and Toxicology, 2019)

The complete chloroplast genome sequence of the wild Chinese chestnut (Castanea mollissima) - Lili Cheng; Wugang Huang; Yanping Lan; Qingchang Cao; Shuchai Su; Zhijun Zhou; Jinbao Wang; Jianling Liu; Guanglong Hu (Conservation Genetics Resources, 2018)

Anti-proliferation effects of ethanolic extracts from Sophora moorcroftiana seeds on human hepatocarcinoma HepG2 cell line - Gang Su; Wenke Yang; Wenbo Meng; Qionghui Wu; Yanping Luo; Xingming Ma; Shen Zhao; Xiaodong Xie; Guang-Qin Guo (Natural Product Research, 2018)

Mineral composition variation in the shells of freshwater mussel Anodonta woodiana at different growth stages - Xiubao Chen; Yanping Su; Hongbo Liu; Tao Jiang; Jian Yang (Invertebrate Reproduction & Development, 2017)

Effects of Calcium and Magnesium Ions on Acute Copper Toxicity to Glochidia and Early Juveniles of the Chinese Pond Mussel Anodonta woodiana - Hongbo Liu; Xiubao Chen; Yanping Su; Ik Joon Kang; Xuchun Qiu; Yohei Shimasaki; Yuji Oshima; Jian Yang (Bulletin of Environmental Contamination and Toxicology, 2016)

Morphological development and growth of the freshwater mussel Anodonta woodiana from early juvenile to adult - Xiubao Chen; Hongbo Liu; Yanping Su; Jian Yang (Invertebrate Reproduction & Development, 2015)

Genetic diversity and demographic history of the endangered and endemic fish (Platypharodon extremus): implications for stock enhancement in Qinghai Tibetan Plateau - Junhu Su; Weihong Ji; Yanping Zhang; Dianne M. Gleeson; Zhongyu Lou; Jing Ren; Yanming Wei (Environmental Biology of Fishes, 2015)

CRP Gene polymorphism contributes genetic susceptibility to dyslipidemia in Han Chinese population - Wenbin Wei; Song Yang; Yingru Qiu; Hairu Wang; Xianghai Zhao; Yanping Zhao; Yun Li; Ming Wu; Yanchun Chen; Wen Wang; Xiaoming Shi; Sijun Liu; et al. (Molecular Biology Reports, 2014)

Metals and Metalloids in the Water–Bloom-Forming Cyanobacteria and Ambient Water from Nanquan Coast of Taihu Lake, China - Yanping Su; Hongbo Liu; Jian Yang (Bulletin of Environmental Contamination and Toxicology, 2012)